Pelaksanaan Dokumentasi Asuhan Keperawatan Di Ruang Rawat Inap Rumah Sakit X Jakarta: Pilot Study - Saraswasta, I Wayan Gede; Hariyati, Rr Tutik Sri; Fatmawati, Umi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
The quality of nursing documentation demonstrates the accountability of nurses in providing nursing care topatients. However, the implementation of nursing documentation at hospital X is 58% still below thestandard so that it is necessary to optimize the implementation of nursing documentation. The purpose of thisstudy is to describe an innovation project to optimize the implementation of nursing documentation. Themethod used was a pilot study of 70 nursing documentation. The process starts from problem identification,problem analysis, plan of action, implementation, and evaluation. The quality of nursing documentation ismeasured using a nursing documentation audit instrument. Implementation in the form of guidelines,standart operational procedure (SOP), socialization, trials, assistance and making video roleplay nursingdocumentation. The results of the study showed an increase in the implementation of nursing documentationby 11.40%. The conclusion is that the implementation of an innovation project can improve theimplementation of nursing documentation. The recommendation is to use a guide, SOP and roleplay videosas a reference in carrying out nursing documentation.